(untitled) (Research, Society and Development, 2021)
Absolute uterine factor infertility (AUFI) refers to women who are unable to conceive or maintain pregnancy due to the absence of the uterus or the presence of an anatomically or physiologically dysfunctional uterus. New strategies have been sought in recent decades to solve this problem, such as uterine transplantation. However, little is known about uterine immunogenicity and there is little data on the immune response to transplanted uterine tissue. Thus, this study aimed to demonstrate how the body’s immune response to uterine transplantation can occur through a literature review. For that, a search was carried out in the SciELO, LILACS, PubMed / MEDLINE and Science Direct databases. According to the data obtained, it is believed that the uterus is an immunoprivileged organ in relation to the rapid immune response exerted by the organism, however the experiences of allogeneic uterine transplantation showed rejection patterns similar to those observed in other solid organ transplants. In general, rejection was characterized by myometrial invasion by neutrophils and macrophages, followed by T cells (mainly CD8 +), followed by necrosis, atrophy and fibrosis. This response has a unique characteristic of being mediated by interactions of the T cell receptor (TCR) with molecules of the donor’s own MHC system. Therefore, with this study it was possible to understand how the possible immune response to uterine transplantation would occur, which can lead to the rejection process.